Modelling the inundation and morphology of the seasonally flooded Mayas Wetlands in the Dinder National Park-Sudan - Hassaballah, K.; Mohamed, Y.; Omer, A.; Uhlenbrook, Stefan (Springer, 2020)
Understanding the spatiotemporal dynamics of surface water in varied, remote and inaccessible isolated floodplain lakes is difficult. Seasonal inundation patterns of these isolated lakes can be misestimated in a hydrodynamic model due to the short time of connectivity. The seasonal and annual variability of the Dinder River flow has great impact on what is so called Mayas wetlands, and hence, on the habitats and the ecological status of the Dinder National Park. This variability produces large morphological changes due to sediment transported within the river or from the upper catchment, which affects inflows to Mayas wetlands and floodplain inundation in general. In this paper, we investigated the morphological dimension using a quasi-3D modelling approach to support the management of the valuable Mayas wetlands ecosystems, and in particular, assessment of hydrological and morphological regime of the Dinder River as well as the Musa Maya. Six scenarios were developed and tested. The first three scenarios consider three different hydrologic conditions of average, wet and dry years under the existing system with the constructed connection canal. While the other three scenarios consider the same hydrologic conditions but under the natural system without an artificial connection canal. The modelling helps to understand the effect of human intervention (connection canal) on the Musa Maya. The comparison between the simulated scenarios concludes that the hydrodynamics and sedimentology of the Maya are driven by the two main factors: a) the hydrological variability of Dinder River; and b) deposited sediment plugs in the connection canal.